Nieformalni opiekunowie osób starszych - doświadczenia i uczucia oraz ich potrzeby związane z pełnioną rolą = Experiences, feelings and needs of informal caregivers of elderly people - Herudzińska, Małgorzata H. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article focuses on personal experiences, feelings and needs related to being an informal caregiver of an elderly person. It uses the existing data as well as data collected by the author in 2019 (targeted selection of informal caregivers for elderly persons; 159 open interviews with a checklist). It was found, among other things, that most informal carers are kinship carers, women, who are more likely to have negative - rather than positive - experiences and feelings. Most of all, caregivers need time, including time to rest, and support.
Keywords: starość; opiekun nieformalny; potrzeby nieformalnych opiekunów osób starych; doświadczenie; uczucia; old age; informal caregiver; experiences; feelings; needs of informal caregivers of elderly people